Post Factum. - De Baere, Bart; ter Braak, Lex ([S.l.] : [s.n.], 1995)
Körmeling, John ; Bade, David ; Post, Liza May ; Koelewijn, Job ; Honoréδ'O ; Kinoshita, Suchan ; Mees, Guy ; Name ; Fink, Christoph ; Schaerf, Eran
Among others... onder anderen, 46e Biennale van Venetië, klooster van San Francesco della Vigna, Venetië, 11 juni tot 2 oktober 1995
boek